ok so i suck at this even though its simple...i tend to over think these things....your help would be much appreciated
2p-3q=6
-2p+3q=-6
It is easy, but you need to find either p or q first and use it to solve for the other one. So, if you have
$\displaystyle
2p-3q=6
$
$\displaystyle -2p+3q=-6
$
Say you want P for the first equation so you have to get P on one side alone...
$\displaystyle 2p-3q=6
$
Divide out your 2 to get P alone.
$\displaystyle 2p/2=6/2+3q/2$
Which reduces to p=3+3q/2
Now, you have P so find Q by putting the value of P in the other equation...
$\displaystyle -2(3+3q/2)+3q=-6$ and I think you can figure out the rest.
Ok, first you take equation 2 and solve for one of the variables.
Let's solve for 'p'.
-2p+3q=-6
-2p=-3q-6
2p=3q+6
p=3/2q+6/2
p=1.5q+3
Now, take the equation and plug it into the variable of the first equation.
2p-3q=6
2(1.5q+3)-3q=6
Now solve the equation for 'q'.
q=1
Now, plug 'q' into the first equation.
2p-3q=6
2p-3(1)=6
2p-3=6
2p=9
p=4.5
Plug in 'p' and 'q' to check you answers in a equation (it doesn't matter if its the ist or second equation.)
Let's use the first since it look the easiest.
2p-3q=6
2(4.5)-3(1)=6 ?
9-3=6 ?
6=6
The answers are equal so you know your answers work.
Hope this helps.